EU investment support for small and medium-sized enterprises in southern Europe: To be recommended? - Bernhard Forstner; Ulrich Koester (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2014)
The president of the European Parliament, Martin Schulz, has repeatedly pointed out that small and medium-sized enterprises (SMEs) in some southern European countries face major constraints to access to credit and that removing these constraints for SMEs could contribute to reducing unemployment. He promised to support special loans programs. According to press reports the European Central Bank is also considering low-cost loans for national banks if they provide credit for SMEs. In this article it is argued theoretically and empirically that the single-business investment support does not address the causes of high unemployment and could result, due to the difficulty in monitoring, in great inefficiencies. Studies that have focused on rural development measures to improve regional economic structures do not show that investment support is an efficient economic policy measure. There are more efficient measures available. An ex-ante evaluation, which is in accordance with EU regulations for the conception of new policies, projects and programs (EU Commission 2006), was conducted to test this recommendation. Any adoption of such policy, should be based on the results of economic analyses and - if available - empirical studies. – – Der Präsident des Europäischen Parlaments, Martin Schulz, hat wiederholt betont, dass kleine und mittelständische Unternehmen nur begrenzten Zugang zu Krediten haben. Eine Förderung dieser Unternehmen sei daher sinnvoll, um die Arbeitslosigkeit zu verringern. Laut Presseberichten erwägt auch die EZB eine verbilligte Kreditvergabe an nationale Banken, wenn diese kleine und mittelständische Unternehmen kreditieren. Im Beitrag wird aus theoretischer Sicht und anhand von Ergebnissen empirischer Untersuchungen argumentiert, dass die einzelbetriebliche Investitionsförderung nicht an den Ursachen der hohen Arbeitslosigkeit ansetzt und aufgrund ihrer schwierigen Steuerbarkeit große Effizienzprobleme aufweist. Untersuchungen der Maßnahmen zur "Förderung der ländlichen Entwicklung", der "Verbesserung der regionalen Wirtschaftsstruktur" sowie der "Ländlichen Entwicklung" belegen nicht, dass Investitionsförderung eine effiziente wirtschaftspolitische Maßnahme ist. Es gibt effizientere Maßnahmen.
urn:nbn:de:gbv:3:2-54825
Keywords: 330